2008
DOI: 10.1080/18811248.2008.9711450
|View full text |Cite
|
Sign up to set email alerts
|

Flow Structure of Subcooled Boiling Water Flow in a Subchannel of 3 × 3 Rod Bundles

Abstract: In this paper, the interfacial flow structure of subcooled water boiling flow in a subchannel of 3 Â 3 rod bundles is presented. The 9 rods are positioned in a quadrangular assembly with a rod diameter of 8.2 mm and a pitch distance of 16.6 mm. Local void fraction, interfacial area concentration, interfacial velocity, Sauter mean diameter, and liquid velocity have been measured using a conductivity probe and a Pitot tube in 20 locations inside one of the subchannels. A total of 53 flow conditions have been con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…The experimental existing databases particular to IAC measurements have been provided extensively by Ishii (2001, 2002), Hibiki et al (2006) and Ozar et al (2008). Among the work presented in these publications, Akita and Yoshida (1974), Liu (1989), Serizawa et al (1991), Roy et al (1994) and Yun et al (2008) provide a valuable experimental database for different flow geometries and wide conditions. Very few reliable data exists in the literature that covers a wide range of flow conditions and flow regimes.…”
Section: Introductionmentioning
confidence: 97%
“…The experimental existing databases particular to IAC measurements have been provided extensively by Ishii (2001, 2002), Hibiki et al (2006) and Ozar et al (2008). Among the work presented in these publications, Akita and Yoshida (1974), Liu (1989), Serizawa et al (1991), Roy et al (1994) and Yun et al (2008) provide a valuable experimental database for different flow geometries and wide conditions. Very few reliable data exists in the literature that covers a wide range of flow conditions and flow regimes.…”
Section: Introductionmentioning
confidence: 97%
“…Besides the databases listed in Tables 5 and 6, several unique and useful data are available in literature. They are boiling flow data in a sub-channel of 3 Â 3 rod bundle (Yun et al, 2008) and interfacial area transport data of vertical upward steam-water twophase flow in an annulus at elevated pressures (Ozar et al, 2013) and interfacial area transport data of vertical upward airewater two-phase flow in an annulus channel (Jeong et al, 2008). More detailed review is found in Lin and Hibiki (2014).…”
Section: Databases Utilized For Validation Of Two-phase Flow Cfdmentioning
confidence: 99%
“…The effective heat removal depends on the complex hydrodynamics of the two‐phase flow around the nuclear rods bundle. The hydrodynamics observed in the nuclear reactor core is complicated owing to the presence of nuclear rods (which is a challenging geometry), and also due to the complex phenomena of bubble nucleation, growth, detachment, and simultaneous motion of bubbles and the liquid phase …”
Section: Introductionmentioning
confidence: 99%